Hamiltonella symbionts benefit whitefly fertilization by regulating the maternal protein Tudor–mediated piRNA pathway - Xiang Sun; Huan Li; Zhan-Bo Chen; Bing-Qi Liu; Chu-Qiao Li; Zheng-Yang Zhao; Xing-Ye Li; Jun-Bo Luan (Proceedings of the National Academy of Sciences, 2025)
Although it is widely recognized that nutritional symbionts can manipulate host reproduction, the underlying molecular and cellular mechanisms are largely unclear. The facultative symbiont Hamiltonella in bacteriocyte induces female-biased sex ratio of whiteflies. Here, we demonstrate that a maternal gene tudor ( tud ) and its encoded protein have lower expression levels in ovaries of Hamiltonella- cured whiteflies. Tud family proteins can interlink the various stages of biosynthesis of PIWI-interacting RNA (piRNA), a class of small noncoding RNAs. We find that Hamiltonella affects the abundance of a piRNA through the maternal gene tud , thereby regulating the expression of the vacuolar ( H+ ) -ATPase H subunit ( VATPH ), which is the switch of activity of the vacuolar (H+)-ATPase that plays a crucial role in maintaining the homeostasis of intracellular energy and supporting mitochondrial respiration. This regulation adjusts the ATP level in ovaries of whiteflies. The ATP level shapes the F-actin pattern in ovaries and eggs of whiteflies, ultimately manipulating whitefly fertilization. Silencing tud inhibited whitefly fertilization by impairing ATP levels and F-actin patterns in ovaries and eggs. This study reveals that symbiont and maternal protein associations can regulate host fertilization by piRNA biosynthesis.